Pemberdayaan Koperasi dan UMKM melalui Pengembangan Sistem Pendukung Usaha dan Pelatihan Digital Marketing di Kabupaten Probolinggo - Ahmad Izzuddin; Yustina Suhandini Tj; Mohammad Iskak Elly; Serlin Velinda; Hikmatul Maulidia; Nadia Putri (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
The community service program implemented in Probolinggo Regency aims to enhance the capacity of cooperatives and MSMEs through the development of a cooperative information system and digital marketing training. The program involved two participant groups: 20 board members and staff of KPRI Waluyo Jati in the information system workshop, and 15 MSME practitioners in the digital marketing training. Post-activity evaluations indicate a significant increase in knowledge among the cooperative group, particularly in understanding basic information system concepts (62.5% slightly increased; 37.5% significantly increased), benefits of information system implementation (50% significantly increased), types of cooperative software (62.5% slightly increased; 37.5% significantly increased), and data security (62.5% significantly increased). All respondents (100%) also reported improved understanding of data analytics, while 56.3% experienced increased knowledge related to information system integration with external stakeholders. Among MSME participants, 80% reported improved digital marketing knowledge, 73.3% felt more prepared to market their products online, and 66.7% experienced an increase in monthly sales turnover. Overall, the program proved effective in strengthening cooperative management capacity and enhancing the digital marketing skills of MSME practitioners, thereby contributing to local economic empowerment.